2009
DOI: 10.1111/j.1600-0404.1975.tb01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy and Neuropathy Associated With Osteomalacia

Abstract: Thirty unselected females with proven osteomalacia were evaluated clinically, electromyographically and histopathologically for muscle dysfunction. Clinical evidence of myopathy was found in all the patients except one; the electromyograms were abnormal in 25 of them, and histopathological abnormalities, although slight and nonspecific, were seen in all the 17 patients who underwent muscle biopsy. Electromyographic findings revealed a myopathic pattern as evidenced by a significant reduction in motor unit pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 19 publications
3
53
0
Order By: Relevance
“…This strong positive association may be explained by the combined action of vitamin D on muscles and nerves. (5)(6)(7)(8)(9)(10)30) Even if the association of vitamin D with muscular strength remains controversial 5,7 -which was confirmed by the lack of significant linear association between serum 25(OH)D and quadriceps strength in our study-its action on muscle contraction speed and muscle power seems likely. (5,30) It has indeed been shown that serum vitamin D concentrations influence muscular phenotypic determinism because fast-twitch muscle fiber atrophy was identified in adults with vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…This strong positive association may be explained by the combined action of vitamin D on muscles and nerves. (5)(6)(7)(8)(9)(10)30) Even if the association of vitamin D with muscular strength remains controversial 5,7 -which was confirmed by the lack of significant linear association between serum 25(OH)D and quadriceps strength in our study-its action on muscle contraction speed and muscle power seems likely. (5,30) It has indeed been shown that serum vitamin D concentrations influence muscular phenotypic determinism because fast-twitch muscle fiber atrophy was identified in adults with vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 58%
“…(31) Additionally, vitamin D is a neurosteroid hormone whose insufficiency may cause disturbances in the peripheral nervous system, such as reduced nerve conduction speed, but also in the central nervous system. (8,9,30,31) For example, vitamin D status has been associated with cognitive function such as attention, which is involved in gait control in older adults. (32)(33)(34)(35)(36) Fast-pace walking is precisely considered as a more attention-demanding task than usual-pace walking, (23,36) which could explain in part the close positive association shown in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations